Avant-propos - Thomas Fressin (Bulletin du Centre de Recherche du Château de Versailles)
The protection of the king, his family and his residences goes beyond security missions alone. The arrangements put in place for royal protection played a fundamental role in the construction of curial pomp, monarchical authority and the maintenance of social order under the Ancien Régime. Serving as the proceedings of the study day on ‘Protecting the King: France, Seventeenth-Eighteenth Century’ organized on 2 December 2023 at Versailles, and supplemented by additional papers, the contributions in this collection offer an analysis of royal protection as an object of study. They provide a multi-dimensional analysis of several units of the King’s Military Household in terms of their functions, their organization, their systems, their resources, their presence in the royal residences and their political role on the curial stage. Through a study of the circles of protection (R. Masson), symbolic spaces such as the Salle des Gardes (M. Viallon), and elite units such as the Musketeers (J. Wilmart) and the bodyguards of the Scottish Company (T. Fressin), the authors show how the King’s Military Household and its men played a central role in the symbolic and functional architecture of royal power. The study of the Gardes-Françaises on the eve of the Revolution (C. Monseigne) and the last days of the monarchy, with the defence of the Château of Versailles by the bodyguards (C. Weiss), highlights the tensions between monarchical loyalty and political upheaval.